Altered brain network centrality in patients with adult comitant exotropia strabismus: A resting-state fMRI study. Issue 1 (January 2018) - Tan, Gang; Dan, Zeng-Renqing; Zhang, Ying; Huang, Xin; Zhong, Yu-Lin; Ye, Lin-Hong; Rong, Rong; Ye, Lei; Zhou, Qiong; Shao, Yi
Objective: To investigate the underlying functional network brain-activity changes in patients with adult comitant exotropia strabismus (CES) and the relationship with clinical features using the voxel-wise degree centrality (DC) method. Methods: A total of 30 patients with CES (17 men, 13 women), and 30 healthy controls (HCs; 17 men, 13 women) matched in age, sex, and education level participated in the study. DC was used to evaluate spontaneous brain activity. Receiver operating characteristic (ROC) curve analysis was conducted to distinguish CESs from HCs. The relationship between mean DC values in various brain regions and behavioral performance was examined with correlation analysis. Results: Compared with HCs, CES patients exhibited decreased DC values in the right cerebellum posterior lobe, right inferior frontal gyrus, right middle frontal gyrus and right superior parietal lobule/primary somatosensory cortex (S1), and increased DC values in the right superior temporal gyrus, bilateral anterior cingulate, right superior temporal gyrus, and left inferior parietal lobule. However, there was no correlation between mean DC values and behavioral performance in any brain regions. Conclusions: Adult comitant exotropia strabismus is associated with abnormal brain network activity in various brain regions, possibly reflecting the pathological mechanisms of ocular motility disorders in CES.